2017 Alzheimer's disease facts and figures. Issue 4 (15th March 2017) - Unknown
Abstract : This article describes the public health impact of Alzheimer's disease (AD), including incidence and prevalence, mortality rates, costs of care, and the overall impact on caregivers and society. The Special Report examines how the use of biomarkers may influence the AD diagnostic process and estimates of prevalence and incidence of the disease. An estimated 5.5 million Americans have Alzheimer's dementia. By mid‐century, the number of people living with Alzheimer's dementia in the United States is projected to grow to 13.8 million, fueled in large part by the aging baby boom generation. Today, someone in the country develops Alzheimer's dementia every 66 seconds. By 2050, one new case of Alzheimer's dementia is expected to develop every 33 seconds, resulting in nearly 1 million new cases per year. In 2014, official death certificates recorded 93, 541 deaths from AD, making AD the sixth leading cause of death in the United States and the fifth leading cause of death in Americans age ≥65 years. Between 2000 and 2014, deaths resulting from stroke, heart disease, and prostate cancer decreased 21%, 14%, and 9%, respectively, whereas deaths from AD increased 89%. The actual number of deaths to which AD contributes is likely much larger than the number of deaths from AD recorded on death certificates. In 2017, an estimated 700, 000 Americans age ≥65 years will have AD when they die, and many of them will die because of the complications caused by AD. In 2016, more than 15 million family members and other unpaid caregivers provided an estimated 18.2 billion hours of care to people with Alzheimer's or other dementias. This care is valued at more than $230 billion. Average per‐person Medicare payments for services to beneficiaries age ≥65 years with Alzheimer's or other dementias are more than three times as great as payments for beneficiaries without these conditions, and Medicaid payments are more than 23 times as great. Total payments in 2017 for health care, long‐term care, and hospice services for people age ≥65 years with dementia are estimated to be $259 billion. In recent years, efforts to develop and validate AD biomarkers, including those detectable with brain imaging and in the blood and cerebrospinal fluid, have intensified. Such efforts could transform the practice of diagnosing AD from one that focuses on cognitive and functional symptoms to one that incorporates biomarkers. This new approach could promote diagnosis at an earlier stage of disease and lead to a more accurate understanding of AD prevalence and incidence.